Review-Recent Advances in Block-Copolymer Nanostructured Subwavelength Antireflective Surfaces - Mir, Sajjad; Mokarian, Parvaneh (My University, 2020)
Nanostructured Anti-Reflective (AR) surfaces have attracted a focused attention during the last few years and offer an alternative to AR coatings. Recent nanopatterning approaches have allowed fabrication of bioinspired nanostructured surfaces with unprecedented broadband and omnidirectional AR properties. However, nanofabrication methods face major challenges for reaching industrial maturity including high capital expenditure cost, scalability, reliability and adaptability of the technologies. Block copolymer (BCP) films provide one way to overcome some of these limitations by offering scalable and versatile masks to fabricate well-defined, uniform and tunable nanostructures on a variety of substrates at a modest price. This article aims at highlighting recent efforts for assembling such AR nanostructured surfaces with BCP films and the challenges yet to tackle prior to commercialization of the technology.
PUBLISHED
Keywords: Sensors; Antireflective; Block-copolymers; Nanostructures